The design of digital marketing strategy with the methods sostac on stratup qtaaruf - Bisri, Mohammad hasan; Sudarmaningtyas, Pantjawati; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Startup Qtaaruf is online taaruf from surabaya. The user active processed on 17-23 october 2017 rise and fall and no access through social media. Based on 5 stages of an integrated digital life cycle marketing startup qtaaruf should be at point “gain position” on search engine , but they at point “gain followers” and “initiate relationships” that focuses increase user .This study attempts to documents produced digital design marketing by using methods SOSTAC consisting of the situation analysis, objectives, strategy, tactics, and action. Model SOSTAC to the training analysis, mapping training strategy strategy to 5s objective, mapping 5s objective strategy to the program, mapping tack to 4p and preparing for further step.The digital design marketing that produces 7 strategy as long as 12 months. Cost divided into 2 model. The first model and that is the ability organic for free, their profits audience will increase only berelasi on followers and following qtaaruf. The second model that is using campaign features cost Rp.7.400.000, their profits the wider audience. Potential reach 2.900.000 people with an estimated daily range 1100-100 audience every week and could lead to the website qtaaruf directly.